Effects of chemotherapy on ultrastructure of oesophageal adenocarcinoma. Issue 11 (November 1992) - Darnton, S J; Antonakopoulos, G N; Newman, J; Matthews, H R
Abstract : AIMS: To compare and contrast the ultrastructural appearance of resected oesophageal adenocarcinomas treated with preoperative chemotherapy with that of non-treated resected controls; and to determine the usefulness of this method in the assessment of the effectiveness of the chemotherapeutic regimen. METHODS: Ten resected oesophageal adenocarcinomas treated with preoperative chemotherapy--mitomycin-C, ifosfamide, and cisplatin (MIC)--were examined by transmission electron microscopy and their appearance compared with that of 13 concurrent untreated resected oesophageal adenocarcinomas. RESULTS: The treated adenocarcinomas showed cytotoxic damage although complete tumour eradication was not achieved. In all 10 treated cases a variable proportion of the neoplastic cells showed unusual degenerative and necrotic changes not seen in untreated cases. In the most affected carcinomas the stroma contained increased numbers of inflammatory cells. CONCLUSIONS: This ultrastructural method is useful for the assessment of the in vivo effect of MIC.